Clinical significance of albumin to globulin ratio among patients with stroke-associated pneumonia - Chen, Lingli; Xu, Minjie; Huang, Qiqi; Liu, Yuntao; Ren, Wenwei (Frontiers in Nutrition, 2022)
Background: It has been proven that the ratio of albumin to globulin (A/G) is a typical biomarker for monitoring inflammation and nutritional status. But the potential role of A/G in stroke-associated pneumonia (SAP) after acute ischemic stroke (AIS) remained unknown. Patients and methods: Following inclusion criteria, 5173 AIS patients were included and segmented into SAP (n=897) and non-SAP (n=4276) groups. The differences in variables between groups were compared. The logistic regression model was used to determine the association between A/G and SAP, and a forest plot was drawn. Results: Compared with the non-SAP group, the SAP group had a lower A/G level (P < 0.001). Then, A/G was divided into quartiles. In comparison to Q3 (A/G=1.25-1.39), logistic regression revealed that patients with a lower A/G (A/G ≤ 1.09) had a higher risk of SAP (OR=1.96, 95% CI, 1.56-2.46, P < 0.001). On the contrary, those with a higher A/G (A/G ≥ 1.4) had a lower SAP risk (OR=0.73, 95% CI, 0.54-0.97, P=0.029). Conclusions: The study revealed that a low A/G level was associated with an increased SAP risk. Appropriate preventative measures for SAP should be taken in AIS patients with a low A/G level.